Pelatihan Tari Srimpi Pandhelori Gaya Yogyakarta di Jakarta: Kontinuitas, Transformasi, dan Strategi Pelestarian - Sulistiani (Program Studi Pendidikan Tari FBS UNJ, 2025)
One way to develop culture, particularly in the field of Yogyakarta-style classical dance, is through training outside the palace walls. One type of dance that can be learned is the Srimpi Pandhelori dance. This dance's existence has spread to various cities such as Jakarta. This study aims to analyze the form of Srimpi Pandhelori dance training conducted by dance communities in Jakarta. Throughout the journey, there has been a transformation in training methods and challenges faced in maintaining traditional values. The method used is ethnochoreology with an approach of literature study, observation, and interviews. The results of the study explain that the training and performance activities carried out by three different institutions are part of a cultural preservation strategy that is adaptive to the times. This study also emphasizes the importance of maintaining the rules as a collective memory that represents Javanese cultural identity. Ultimately, it is recommended that the Srimpi Pandhelori Dance training strategy in Jakarta continue to be developed by utilizing digital technology more optimally.